Investigation of the elevation of saltwater wedge due to subsurface dams. Issue 22 (27th August 2020) - Chang, Qinpeng; Zheng, Tianyuan; Chen, Youyuan; Zheng, Xilai; Walther, Marc
Abstract: Subsurface dams are rather effective and used for the prevention of saltwater intrusion in coastal regions around the world. We carried out the laboratory experiments to investigate the elevation of saltwater wedge after the construction of subsurface dams. The elevation of saltwater wedge refers to the upward movement of the downstream saltwater wedge because the subsurface dams obstruct the regional groundwater flow and reduce the freshwater discharge. Consequently, the saltwater wedge cannot further extend in the longitudinal direction but rises in the vertical profile resulting in significant downstream aquifer salinization. In order to quantitatively address this issue, field‐scale numerical simulations were conducted to explore the influence of various dam heights, distances, and hydraulic gradients on the elevation of saltwater wedge. Our investigation shows that the upward movement of the saltwater wedge and its areal extension in the vertical domain of the downstream aquifer become more severe with a higher dam and performed a great dependence on the freshwater discharge. Furthermore, the increase of the hydraulic gradient and the dam distance from the sea boundary leads to a more pronounced wedge elevation. This phenomenon comes from the variation of the freshwater discharge due to the modification of dam height, location, and hydraulic gradient. Large freshwater discharge can generate greater repulsive force to restrain the elevation of saltwater wedge. These conclusions provide theoretical references for the behaviour of the freshwater–seawater interface after the construction of subsurface dams and help optimize the design strategy to better utilize the coastal groundwater resources. Abstract : The elevation of saltwater wedge refers to the upward movement of the downstream saltwater wedge after the construction of subsurface dams. The subsurface dams obstruct the regional groundwater flow and decrease the freshwater discharge. Then the saltwater wedge cannot advance in the longitudinal direction due to the block of the dam but rises in the vertical profile because of the reduced freshwater discharge, which eventually increases the saltwater contaminated area in the downstream aquifer.